Analisis dan Perancangan Aplikasi Mobile guna Kegiatan Mentoring berbasis Online - Ayu Amalia; Suhendi Suhendi (LPPM STT Terpadu Nurul Fikri, 2021)
Globalization makes human resources one of the qualities or advantages that become a parameter in the competition between countries in the world. To produce superior human resources, an experienced mentor is needed who can act as an advisor and role model, also known as a mentor. To bring together the two parties, namely mentors and mentees, an e-learning prototype was designed to solve problems between users and according to user needs. This prototype uses the prototype design of the Figma design application and uses the Unified Modeling Language (UML) to design the design needs of user features and the process flow that occurs. Making this prototype utilizing a data collection method based on literature review for reference in the early stages of research, then taking samples from the Mentor and Mentee needs analysis questionnaire to 113 respondents consisting of the general public who received formal and non-formal education and 85 out of 113 respondents stated that need these prototypes. The author also evaluates the prototypes that have been built with the help of targeted Mentor and Mentee users, and the average results are agreed if the entire display of the function prototype can be understood and the business flow in it can be followed.